Molecular Signatures for the PVC Clade (Planctomycetes, Verrucomicrobia, Chlamydiae and Lentisphaerae) of Bacteria Provide Insights into their Evolutionary Relationships - Gupta, Radhey S.; Bhandari, Vaibhav; Naushad, Hafiz S. (Frontiers in Microbiology, 2012)
The PVC superphylum is an amalgamation of species from the phyla Planctomycetes, Verrucomicrobia, and Chlamydiae, along with the Lentisphaerae, Poribacteria, and two other candidate divisions. The diverse species of this superphylum lack any significant marker that differentiates them from other bacteria. Recently, genome sequences for 37 species covering all of the main PVC groups of bacteria have become available. We have used these sequences to construct a phylogenetic tree based upon concatenated sequences for 16 proteins and identify molecular signatures in protein sequences that are specific for the species from these phyla or those providing molecular links among them. Of the useful molecular markers identified in the present work, six conserved signature indels (CSIs) in the proteins Cyt c oxidase, UvrD helicase, urease, and a helicase-domain containing protein are specific for the species from the Verrucomicrobia phylum; three other CSIs in an ABC transporter protein, cobyrinic acid ac-diamide synthase, and SpoVG protein are specific for the Planctomycetes species. Additionally, a 3 aa insert in the RpoB protein is uniquely present in all sequenced Chlamydiae, Verrucomicrobia, and Lentisphaerae species, providing evidence for the shared ancestry of the species from these three phyla. Lastly, we have also identified a conserved protein of unknown function that is exclusively found in all sequenced species from the phyla Chlamydiae, Verrucomicrobia, Lentisphaerae, and Planctomycetes suggesting a specific linkage among them. The absence of this protein in Poribacteria, which branches separately from other members of the PVC clade, indicates that it is not specifically related to the PVC clade of bacteria. The molecular markers described here in addition to clarifying the evolutionary relationships among the PVC clade of bacteria also provide novel tools for their identification and for genetic and biochemical studies on these organisms.